Manejo del TEC - Yáñez, Alfredo (Revista Hospital Clínico Universidad de Chile, 1997)
Management of the head injured patientThe treatmenl in the acute phase of a patient with a severe head injury and coma require inmediate neurologic attention and, often resuscitation. There is often pupillary enlargement or asymmetry. Persistent unresponsiveness is a grave sign. After the patient is cadiorrespiratory stabilized, attention is given to life-threatening noncranial injuries, followed by a survey neurologic examination.